Tillage and N Impact on Wheat Production and N Efficiency under Rice-Wheat Cropping System in Northwestern Pakistan - Usman, Khalid; Khalil, Shad Khan; Ghulam, Said (2012)
We examined the effect of tillage (T) systems [zero (ZT), reduced (RT) and conventional tillage (CT)] and N rates (0, 80, 120, 160 and 200 kg ha-1) on wheat yield and N efficiency in northwestern Pakistan. Tillage systems produced similar grain yield and N efficiency indices (NEI) except nitrogen harvest index (NHI). Grain yield increased with increase in N, while grain to straw N ratio, N utilization efficiency (NUtE) and NHI decreased with N. Zero tillage having higher NHI may have the potential for higher yield compared with RT and CT if provided with optimum N. ZT with 160 kg N ha-1 may be a more efficient and sustainable strategy to enhance wheat yield and NEI.
Keywords: Wheat--Yields.; Tillage